Development and Dissemination of a Strengths-Based Indigenous Children's Storybook: “Our Smallest Warriors, Our Strongest Medicine: Overcoming COVID-19” - O'Keefe, Victoria M.; Maudrie, Tara L.; Ingalls, Allison; Kee, Crystal; Masten, Kristin L.; Barlow, Allison; Haroz, Emily E. (Frontiers in Sociology, 2021)
The traditions, strengths, and resilience of communities have carried Indigenous peoples for generations. However, collective traumatic memories of past infectious diseases and the current impact of the coronavirus disease 2019 (COVID-19) pandemic in many Indigenous communities point to the need for Indigenous strengths-based public health resources. Further, recent data suggest that COVID-19 is escalating mental health and psychosocial health inequities for Indigenous communities. To align with the intergenerational strengths of Indigenous communities in the face of the pandemic, we developed a strengths- and culturally-based public health education and mental health coping resource for Indigenous children and families. Using a community-engaged process, the Johns Hopkins Center for American Indian Health collaborated with 14 Indigenous and allied child development, mental health, health communications experts and public health professionals, as well as a Native American youth artist. Indigenous collaborators and Indigenous Johns Hopkins project team members collectively represented 12 tribes, and reservation-based, off-reservation, and urban geographies. This group shared responsibility for culturally adapting the children’s book “My Hero is You: How Kids Can Fight COVID-19!” developed by the Inter-Agency Standing Committee Reference Group on Mental Health and Psychosocial Support in Emergency Settings and developing ancillary materials. Through an iterative process, we produced the storybook titled “Our Smallest Warriors, Our Strongest Medicine: Overcoming COVID-19” with content and illustrations representing Indigenous values, experiences with COVID-19, and strengths to persevere. In addition, parent resource materials, children’s activities, and corresponding coloring pages were created. The book has been disseminated online for free, and 42,364 printed copies were distributed to early childhood home visiting and tribal head start programs, Indian Health Service units, tribal health departments, intertribal and urban Indigenous health organizations, Johns Hopkins Center for American Indian Health project sites in partnering communities, schools, and libraries. The demand for and response to “Our Smallest Warriors, Our Strongest Medicine: Overcoming COVID-19” demonstrates the desire for Indigenous storytelling and the elevation of cultural strengths to maintain physical, mental, emotional, and spiritual health during the COVID-19 pandemic.